Evaluation of the AR4 CMIP3 and the AR5 CMIP5 Model and Projections for Precipitation in Northeast Brazil - Alves, José M. B.; Vasconcelos Junior, Francisco C.; Chaves, Rosane R.; Silva, Emerson M.; Servain, Jacques; Costa, Alexandre A.; Sombra, Sérgio S.; Barbosa, Augusto C. B.; dos Santos, Antonio C. S. (Frontiers in Earth Science, 2016)
With the simulations of the models used in the latest reports from the Intergovernmental Panel on Climate Change (IPCC), comparative studies are necessary between observations and the so-called historical run (C20) and future projections of the AR4 (A2) and AR5 (RCP8.5) experiments, in order to assess whether the AR5 models had a better performance in the representation of physical processes. This article compares the sensitivity of IPCC models (AR4 and AR5) in representing the anuall average and seasonal rainfall variation (summer and autumn) in three regions of the Northeast of Brazil between 1979 and 2000, using the CMAP - CPC (Merged Analysis of Precipitation) data as reference. The projections made by these models for the period 2040-2070 were also analyzed.